Attention deficit hyperactivity disorder and autism spectrum disorder in children born to mothers with thyroid dysfunction: a Danish nationwide cohort study. (10th March 2014) - Andersen, SL; Laurberg, P; Wu, CS; Olsen, J
Abstract : Objective: To examine the association between maternal hyper‐ and hypothyroidism and the risk of attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) in the child. Design: A population‐based cohort study. Setting: Singletons liveborn in Denmark between 1991 and 2004. Population: A total of 857 014 singletons alive and living in Denmark at the age of 3 years. Methods: Information on the diagnosis and/or treatment of maternal thyroid disease and the neurodevelopmental disorders ADHD and ASD in the child was obtained from Danish nationwide registers. The Cox proportional hazards model was used to estimate the hazard ratio (HR) with 95% confidence interval (95% CI) for risk of ADHD and ASD in children born to mothers with thyroid dysfunction, adjusting for potential confounding factors. Main outcome measures: ADHD and ASD in the child. Results: Altogether, 30 295 singletons (3.5%) were born to mothers with thyroid dysfunction. Maternal hyperthyroidism diagnosed and treated for the first time after the birth of the child increased the risk of ADHD in the child (adjusted HR 1.23; 95% CI 1.05–1.44), whereas hypothyroidism increased the risk of ASD (adjusted HR 1.34; 95% CI 1.14–1.59). No significant association was seen for maternal diagnosis and treatment prior to the birth of the child. Conclusions: Children born to mothers diagnosed and treated for the first time for thyroid dysfunction after their birth may have been exposed to abnormal levels of maternal thyroid hormone already present during the pregnancy, and this untreated condition could increase the risk of specific neurodevelopmental disorders in the child.